CLINICAL COURSE, PROGNOSIS AND THERAPY OF CHRONIC HEART FAILURE IN PATIENTS WITH NORMAL SYSTOLIC AND DIASTOLIC LEFT VENTRICLE FUNCTION - I. A. Sharoshina; B. A. Sidorenko; Y. V. Konev; N. E. Romanova; N. A. Ivanova; D. V. Preobrazhensky (Российский кардиологический журнал, 2003)
Clinical course, prognosis and therapy of chronic heart failure in patients with normal systolic and diastolic left ventricle function.